Analisa Sistem Registrasi di Obyek Wisata Nimo Highland Pangalengan Bandung - Frisiska; Sri Indrayanti; Ratih Dwi Astuti; Oceu Apristawijaya (Bulletin of Community Engagement, 2024)
The implementation of the registration system at the Nimo Highland Tourist Location, Pangalengan Bandung has been implemented well as a standard. Starting from the ticket purchasing process to the ticket exchange procedure, it has been carried out well. To overcome the surge in visitors during high season, Nimo Highland management has prepared a good registration system. From the results of this research, it can be seen that there are still many queues of tourists visiting the glass sky bridge tourist attraction in the ticketing section because there is only one ticket purchasing door. This certainly makes visitors feel bored if they wait too long. Even psychologically, they are worried about losing the opportunity to do other scheduled activities. This journal analyzes in detail the implementation of the registration system on the Nimo Highland and Nimo Sky Bridge, the Glass Bridge.